2015
DOI: 10.1371/journal.pntd.0003607
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Leptospiral Serogroups Circulating among Humans, Livestock and Wildlife in Katavi-Rukwa Ecosystem, Tanzania

Abstract: BackgroundLeptospirosis is a worldwide zoonotic disease and a serious, under-reported public health problem, particularly in rural areas of Tanzania. In the Katavi-Rukwa ecosystem, humans, livestock and wildlife live in close proximity, which exposes them to the risk of a number of zoonotic infectious diseases, including leptospirosis.Methodology/Principal FindingsA cross-sectional epidemiological study was carried out in the Katavi region, South-west Tanzania, to determine the seroprevalence of Leptospira spp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
55
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 28 publications
14
55
4
Order By: Relevance
“…The microscopic agglutination test (MAT) was used to determine presence of anti-Leptospira antibodies; in accordance with the OIE standards (13). A panel of 11 serovars ( Table 1) representing 11 serogroups previously described as prevalent in Uganda (9) and those shown to be prevalent or maintained in cattle elsewhere in East Africa (14,15) was employed. Briefly, seven day old live Leptospira cultures were used to screen the serum samples at an initial dilution of 1:50.…”
Section: Serological Testingmentioning
confidence: 99%
“…The microscopic agglutination test (MAT) was used to determine presence of anti-Leptospira antibodies; in accordance with the OIE standards (13). A panel of 11 serovars ( Table 1) representing 11 serogroups previously described as prevalent in Uganda (9) and those shown to be prevalent or maintained in cattle elsewhere in East Africa (14,15) was employed. Briefly, seven day old live Leptospira cultures were used to screen the serum samples at an initial dilution of 1:50.…”
Section: Serological Testingmentioning
confidence: 99%
“…These findings are consistent with those of Moch et al (1975), who found seroprevalence of 8.3% in Ethiopia but differ from those of Mgode et al (2015) who reported 39% prevalence in dogs. A possible explanation to the findings by Mgode et al (2015) is that, all the reactors at titres 1: 20 were considered positive while in this study, only reactors with a titre 1:160 were considered positive (Cole et al, 1973;Assenga et al, 2015). According to Miller et al (2011), there is no consensus on cut off titre that constitutes seropositivity by MAT in leptospirosis.…”
Section: Discussionmentioning
confidence: 72%
“…Further doubling dilutions (1:20 to 1:160) were prepared in subsequent wells and then 50 μl of the fully-grown serovars in EMJH medium was added to the sera in the microtiter plate wells and mixed gently and then incubated at 30°C for 2 h. The serum antigen mixture was then visualized by DF microscopy for the presence of agglutination and the titres recorded. A sample was considered positive if 50% or more of the microorganisms in the microtiter well agglutinated at the titre 1:160 (Assenga et al, 2015). This was determined by comparing 50% of spirochaetes, which remained free with a control culture diluted 1:2 with PBS (Korver, 1992).…”
Section: Antibody Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, understanding the zoonotic potential of livestock RVA is of particular interest in Tanzania as, currently, the potential sharing of RVA genotypes between humans and animals remains unknown. In the rural areas of developing countries, including Tanzania, people live in close proximity to animals and sanitation, and hygiene may be poor, thus increasing the risk of zoonotic rotavirus infection [68]. Infected animals or humans shed over 10 billion infectious rotavirus particles per gram/milliliter stool [69], thus contaminating environmental objects.…”
Section: Trends In Rotavirus Genetic Diversity In Tanzaniamentioning
confidence: 99%